Diethoxymethyl Protected Indoles: Synthesis and Regioselective Transformations - Gmeiner, Peter; et al. (Synthesis-Stuttgart, 1996)
Reaction of the indoles 1a-d with triethyl orthoformate gives access to the N-diethoxymethyl derivatives 2a-d. Convenient and mild removal of the diethoxymethyl substituent is possible by subsequent treatment of 2a-d with aqueous HCl and NaOH. Using 2a as an example, it could be shown that deprotonation followed by addition of an electrophile (Me3SiCl or Bu3SnCl) leads to substitution in position 2. Further functionalization was possible by palladium-catalyzed coupling reactions starting from the stannane 4. The diethoxymethyl protected η6-tricarbonylchromium complex 5 facilitated acylation in position 2 after deprotonation.
UnivIS-Import:2015-03-05:Pub.1996.nat.dchph.lphch.dietho